Perlindungan Konsumen atas Iklan Menyesatkan Produk Kecantikan pada Marketplace Perspektif Undang-Undang No. 8 Tahun 1999 dan Fatwa DSN-MUI No. 146 Tahun 2021 Tentang Online Shop Berdasarkan Prinsip Syariah - Rizwani Dara Betha; Annisa Sativa (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2026)
The expansion of beauty products in the marketplace has triggered a rise in misleading advertising, such as the Unitary brand's profiteering of competitors' UV Cam test results to attract consumer purchasing power. This action is detrimental to consumers due to the incompatibility of scientific claims with actual product performance. This research aims to explain legal protection for consumers regarding misleading visualizations through the perspective of Law Number 8 of 1999 and DSN-MUI Fatwa No. 146 of 2021. This research uses a normative juridical method with a statutory approach and a conceptual approach. The results of this research indicate that the use of competitor test results violates the prohibition on misleading advertising in Article 9 paragraph 1 UUPK which has implications for criminal sanctions and compensation obligations. According to sharia, misleading advertising damages the principle of consent (‘an tarāḍin) due to a defect of will in the transaction. Because there is no court decision yet, the restoration of consumer rights is focused entirely through khiyār al-‘ayb, which gives consumers full freedom to cancel the contract (fasakh) in order to avoid material losses and medical risks.